2021
DOI: 10.1108/dlp-09-2020-0095
|View full text |Cite
|
Sign up to set email alerts
|

Assessing large-scale digitization using Web analytics

Abstract: Purpose The purpose of this study is to assess the use of digital collections created via the large-scale digitization of archival collections. The large-scale digitization method specifically examined is the reuse of archival description from finding aids to create digital collections that consist mainly of compound digital objects, equivalent to a folder of items, minimally described at the aggregate level. This paper compares Web analytics data for two large-scale digital collections and one digital collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In 2016, several researchers summarized the most important methods for data mapping, analyzed examples of data mapping applications, such as intelligent research, social media, deep questions and verticals, and suggested that data mapping should consider open topics. In particular, the accuracy of data retrieval, the database's stability and the scenarios' scope (Lapworth, 2021). In addition, some researchers have analyzed approaches related to data mapping inference and Q&A systems to identify development issues related to data mapping inference and Q&A approaches.…”
Section: Related Workmentioning
confidence: 99%
“…In 2016, several researchers summarized the most important methods for data mapping, analyzed examples of data mapping applications, such as intelligent research, social media, deep questions and verticals, and suggested that data mapping should consider open topics. In particular, the accuracy of data retrieval, the database's stability and the scenarios' scope (Lapworth, 2021). In addition, some researchers have analyzed approaches related to data mapping inference and Q&A systems to identify development issues related to data mapping inference and Q&A approaches.…”
Section: Related Workmentioning
confidence: 99%